The relationship between hyperphagia and increased intracranial pressure: A new look at obesity treatment: Intracranial pressure-hyperphagia - Guzelyuz, Betul; Özdemir , Faruk (Journal of Surgery and Medicine, 2026)
Some diseases that progress with excessive intracranial pressure, such as pseudotumor cerebri, are associated with obesity. A 64-year-old female who was admitted to the hospital with a complaint of weight gain was diagnosed with pseudotumor cerebri. She had had a lumboperitoneal shunt for 10 years, and it had stopped working. It was challenging to determine whether the shunt tip, observed between abdominal fat layers and obscured by pseudomembranes, had become functionally shortened due to the patient’s weight gain and had failed to reach the peritoneal cavity, or whether long-standing pseudomembrane obstruction had impaired drainage of cerebrospinal fluid. The latter situation may have led to increased intracranial pressure, subsequently triggering hyperphagia and contributing to the patient’s further weight gain. Based on this clinical example, demonstrating that excessive intracranial pressure is associated with hyperphagia may inform novel approaches to obesity management.